Manajemen Kurikulum Pendidikan - Sulkifli, Sulkifli; Mukmina Amna, Annisa; Mauliana, Lilis; Arief Syamsari, Ilham (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2025)
Education holds a vital role in shaping high-quality human resources and serves as a central component in guiding learning processes. This study aims to explore the concept of curriculum management and its application within Indonesia’s education system. Employing a qualitative literature review approach, the research draws on various sources including books, academic journals, and official policy documents. The findings reveal that curriculum management encompasses conceptualization, planning, execution, and evaluation to ensure an effective learning process. The curriculum framework integrates key components such as objectives, learning content, methods, and assessments, all of which are interconnected to support optimal educational outcomes. The evolution of Indonesia’s curriculum—from the 1947 model to the current Merdeka (Independence) Curriculum—demonstrates the nation's commitment to refining its educational vision and adapting to contemporary challenges. Quality assurance emerges as a crucial factor in enhancing education standards. The study concludes by stressing the importance of collaboration among the government, educational institutions, and the wider community in managing the curriculum to effectively respond to global developments